2014
DOI: 10.1091/mbc.e13-08-0464
|View full text |Cite
|
Sign up to set email alerts
|

FAP20 is an inner junction protein of doublet microtubules essential for both the planar asymmetrical waveform and stability of flagella inChlamydomonas

Abstract: The question of what proteins compose the junctions between two tubules in doublet microtubules is long-standing. Here a conserved flagellar protein, FAP20, is shown to be an inner junction component important for stabilizing the axoneme and scaffolding intra–B-tubular structures required for a planar asymmetrical waveform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
147
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(163 citation statements)
references
References 67 publications
(113 reference statements)
9
147
1
Order By: Relevance
“…FAP20 was proposed to be a candidate for the non-tubulin continuous density by cryo-electron tomography combined with protein tagging9. In our structure, we were not able to observe this density (Fig.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…FAP20 was proposed to be a candidate for the non-tubulin continuous density by cryo-electron tomography combined with protein tagging9. In our structure, we were not able to observe this density (Fig.…”
Section: Resultsmentioning
confidence: 57%
“…4d). Second, Yanagisawa et al 9. recently proposed that in Chlamydomonas , tektin forms the inner junction non-tubulin structure together with FAP20 and PACRG.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that PACRG interacts with the axonemal protein FAP20, localized at the inner junction of doublet microtubules (Yanagisawa et al ., 2014). This location is near the root of the RSs on the A2 and A3 protofilaments (Nicastro et al ., 2006; Barber et al ., 2012); therefore, it is possible that PACRG and its interactors are involved in relaying signals from the CA and RSs to the inner dynein arms.…”
Section: Resultsmentioning
confidence: 99%
“…Additional studies have suggested that Rib72, PACRG (the Parkin co-regulated gene product), FAP252, and FAP20 form a complex which is anchored to the doublet microtubules (Ikeda et al ., 2007; Yanagisawa et al ., 2014). Rib72 was simultaneously discovered by three different labs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation